Preparation of Imazethapyr Surface Molecularly Imprinted Polymers for Its Selective Recognition of Imazethapyr in Soil Samples - Yanqiang Zhou; Yinhui Yang; Meihua Ma; Zhian Sun; Shanshan Wu; Bolin Gong (Journal of Analytical Methods in Chemistry)
A novel strategy based on imazethapyr (IM) molecular-imprinting polymers (MIPs) grafted onto the surface of chloromethylation polystyrene resin via surface-initiated atom transfer radical polymerization (SI-ATRP) for specific recognition and sensitive determination of trace imazethapyr in soil samples was developed. The SI-ATRP was performed by using methanol-water (4 : 1, v/v) as the solvent, acrylamide as the functional monomer, trimethylolpropane trimethacrylate (TRIM) as the cross-linker, imazethapyr as the template, and CuBr/2,2′-bipyridine as the catalyst. The resulting MIPs were characterized by elemental analysis, Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Then, the binding selectivity, adsorption capacity, and reusability of the MIPs were evaluated. The results indicated that the prepared MIPs exhibited specific recognition and high selectivity for imazethapyr. The MIPs were further used as solid-phase extraction (SPE) materials coupled with high-performance liquid chromatography (HPLC) for selective extraction and detection of trace imazethapyr from soil samples. The results showed that good linearity was observed in the range of 0.10–5.00 μg/mL, with a correlation coefficient of 0.9995. The limit of detection (LOD) of this method was 15 ng/g, and the extraction recoveries of imazethapyr from real samples were in the range of 91.1–97.5%, which proved applicable for analysis of trace imazethapyr in soils. This work proposed a sensitive, rapid, and convenient approach for determination of trace imazethapyr in soil samples.